Thickness-dependent Magnetic Domain Structures in Epitaxial FePd Films - Kim, JinBae; Choi, Jun Woo; Kim, Hyung-Jun; Cho, Sang-Geun; Kim, Jongryoul; Kim, Hyeon Seung (KOREAN PHYSICAL SOC, 2012)
We present the results of a systematic change in magnetic domain structures. The change depended on the FePd layer thickness of the epitaxial FePd films and was investigated by using magnetic force microscopy. As the FePd layer thickness increased, the width of the domains was observed to decrease. From these results, the change in the perpendicular magnetic anisotropy and the change of the domain width can be ascribed to an increase in the shape anisotropy. The magnetic contrasts observed in tilt-scanning magnetic force microscopy images of the FePd films were attributed to stray fields from the ends of perpendicular magnetic domains.
Keywords: FEPD(001) THIN-FILMS; LAYER THICKNESS; ANISOTROPY